Appropriating the revolution: Emerson and the ideal return - Lewis, Patrick J. (Kansas State University, 2008)
Ralph Waldo Emerson’s early life and education led him to focus on self-development and social concerns. His subsequent individualism and concern for society were not just characteristics of his own personal behavior, but of his vision for the world. The individual and the social form a symbiotic relation critical to understanding this vision. Once Emerson had fully established this vision, he sought to make it known in an attempt to improve American society, which he felt was degenerate and in decline. Emerson suggests that the source of his rejuvenating vision can be found in the principles and ideas of the American Revolution. Emerson appeals to ideals and practice common during the Revolution and immediate post-Revolutionary period. Americans slowly drifted away from practicing these Revolutionary ideals. Emerson appropriates Revolutionary ideals and characteristics to create individual and social change in the America of his day. While this program for change seems clear and straightforward, it becomes problematic when actually applied.
Keywords: Emerson; Revolution; History, United States (0337); Literature, American (0591)